Emotional suffering personal intervention: preliminary results of the study on the health and quality of life at work in the trades sector help and care at home - Soazig Disquay; Angel Egido (Revista de Psicología, 2019)
Old aged people have new needs due to longer life expectancy. Consequently home care interventions are becoming more frequent and professionals are facing changes and new challenges. This paper deals with the psychosocial risks that home care professionals have to face. Asample of 38 professionals was analyzed. Preliminary results are presented. The expression of an emotional suffering emerges, in which the isolation of the participants is one of the factors that characterize the identified occupations to a strong relational dimension with vulnerable people, in those that the contact and perspective of attendance are presented as sources of satisfaction of the occupation and, at the same time sources of complexity, being able to drive to a difficulty of negotiating the not foreseen events.